FUZZY TAKAGI-SUGENO-KANG FOR MENTAL HEALTH CONSULTATION RECOMMENDATIONS - Nawindah Nawindah; Saskia Lydiani (Jurnal Ilmiah Teknologi Infomasi Terapan, 2021)
The condition of students experiencing trauma makes consultation a necessity, there is no mental health examination that can be accessed by students, parents, psychologists, student affairs using the fuzzy Takagi-Sugeno-Kang method so it is necessary to be able to create a recommendation system for student mental health consultations by using fuzzy Takagi-Sugeno-Kang. In accordance with the case given, each student with a neurosis score of 8, psychoactive substances 11, psychotic 10 and post stress trauma disorder 13 had a mental health symptom level of 24.28, meaning they were at a moderate level. With a mental health recommendation system, it can be handled earlier so that learning activities can run according to the desired achievements.